New genera and species of the tribe Parahiraciini (Hemiptera: Fulgoroidea: Issidae) - Gnezdilov, Vladimir M. (Acta entomologica slovenica (Ljubljana), 2005)
Opisana sta dva nova rodova in dve novi vrsti plemena Parahiraciini Cheng & Yang iz Indije in Kitajske - Pinocchias natus in Narinosus nativus.
Keywords: Hemiptera; India; Indija; insekti; Kitajska